2D Metal–Organic Framework Nanosheets with Time‐Dependent and Multilevel Memristive Switching. (14th November 2018) - Ding, Guanglong; Wang, Yaxin; Zhang, Guixian; Zhou, Kui; Zeng, Kelin; Li, Zongxiao; Zhou, Ye; Zhang, Chen; Chen, Xiaoli; Han, Su‐Ting
Abstract: Metal–organic framework (MOF) nanosheets have attracted significant interests for sensing, electrochemical, and catalytic applications. Most significantly, 2D MOF with highly accessible sites on the surface is expected to be applicable in data storage. Here, the memory device is first demonstrated by employing M‐TCPP (TCPP: tetrakis(4‐carboxyphenyl)porphyrin, M: metal) as resistive switching (RS) layer. The as‐fabricated resistive random access memory (RRAM) devices exhibit a typical electroforming free bipolar switching characteristic with on/off ratio of 10 3, superior retention, and reliability performance. Furthermore, the time‐dependent RS behaviors under constant voltage stress of 2D M‐TCPP–based RRAMs are systematically investigated. The properties of the percolated conducting paths are revealed by the Weibull distribution by collecting the measured turn‐on time. The multilevel information storage state can be gotten by setting a series of compliance current. The charge trapping assisted hopping is proposed as operation principle of the MOF‐based RRAMs which is further confirmed by atomic force microscopy at electrical modes. The research is highly relevant for practical operation of 2D MOF nanosheet–based RRAM, since the time widths, magnitudes of pulses, and multilevel‐data storage can be potentially set. Abstract : The 2D MOFs (M‐TCPP) nanosheet–based resistive random access memory device with a typical bipolar switching behavior can obtain excellent multilevel information storage performance by setting different I CC during SET process. The device conforms the percolated conducting paths model verified by the Weibull distribution. The resistance switching mechanism is strongly related to charge trapping assist hopping process verified by Kelvin probe force microscopy and conductive atomic force microscopy.